2000
DOI: 10.1021/ja993486w
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Electronic Structure in Thiolate Self-Assembled Monolayers:  Implication for Molecular Electronics

Abstract: Thiolate self-assembled monolayers (SAMs) on metal surfaces have been explored recently to address the assembly and connection issue in molecular electronics. In these systems, the molecule-metal contact is detrimental to electron transport. This is manifested not only in contact resistance, but also in the nature of the molecular device, which depends on the extent of wave function mixing between the molecule and the metal surface. We probe interfacial electronic structure, particularly unoccupied electronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
65
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(81 citation statements)
references
References 48 publications
(121 reference statements)
16
65
0
Order By: Relevance
“…The authors assigned this feature to the unoccupied r ⁄ resonance of the sulfur-gold bond, following the interpretation of prior 2PPE studies of thiolates on Cu (111) [19] and Ag (111) [20]. The spectral asymmetry was not considered in this work and consequently not related to any additional electron orbital.…”
Section: Resultsmentioning
confidence: 93%
“…The authors assigned this feature to the unoccupied r ⁄ resonance of the sulfur-gold bond, following the interpretation of prior 2PPE studies of thiolates on Cu (111) [19] and Ag (111) [20]. The spectral asymmetry was not considered in this work and consequently not related to any additional electron orbital.…”
Section: Resultsmentioning
confidence: 93%
“…This method has also been used for the study of hot electron dynamics of metals 21 and semiconductors, 22 and to probe the electronically excited states and the dynamics of atoms and molecules adsorbed metal surfaces. [23][24][25][26][27][28] In recent years, 2PPE has been applied to investigate the surface electron dynamics of molecular adsorbed metal oxide surfaces. 29 In this work, we have used a recently developed femtosecond 2PPE apparatus to study the methanol/ TiO 2 (110) photochemistry.…”
Section: Femtosecond 2ppe Experimental Methodsmentioning
confidence: 99%
“…[7] In a quite different (experimental) context, Vondrak et al concluded from their two-photon photoelectron spectroscopy results, backed up by theoretical calculations, that while S ªalligator clipsº may be conducting for hole transport across conjugated (p-bonded) molecules, they can be insulating for electron transport. [78] …”
Section: Molecules Between Bulk Surfaces and Nanoparticlesmentioning
confidence: 99%